2010
DOI: 10.1111/j.1535-7511.2009.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging Models of Acute Seizures and Epilepsy

Abstract: Aged animals have been used by researchers to better understand the differences between the young and the aged brain and how these differences may provide insight into the mechanisms of acute Models of Acute Seizures in Aged MiceIn aged animals, the most commonly used models employ electrical stimulation or a convulsant agent, such as kainic acid, pilocarpine, or pentylenetetrazol, to induce acute seizures. Depending on the model and the animal strain used, the results of studies of acute seizures in aged anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
1
27
1
Order By: Relevance
“…Young age was also reported as 1 of the predictors of seizures in viral or nonspecific encephalitis in human studies . These results are in contrast to data obtained from studies on animal models, where older rats were found more susceptible to seizure induction than their younger counterparts …”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Young age was also reported as 1 of the predictors of seizures in viral or nonspecific encephalitis in human studies . These results are in contrast to data obtained from studies on animal models, where older rats were found more susceptible to seizure induction than their younger counterparts …”
Section: Discussioncontrasting
confidence: 72%
“…34 These results are in contrast to data obtained from studies on animal models, where older rats were found more susceptible to seizure induction than their younger counterparts. 35,36 In a previous study of Pugs with NME, all dogs presented with seizures. 37 Unfortunately, due to the low number of cases with a confirmed histopathological diagnosis in the present study, it was not possible to evaluate the effect of type of inflammatory CNS disease (NME versus GME) on PEE.…”
Section: Antiepileptic Treatmentmentioning
confidence: 97%
“…We suspect this to be part of an age‐dependent increase in seizure susceptibility. Although similar correlations between aging and seizure susceptibility have been previously reported for both mammals and Drosophila, the origins of this phenomena remain to be resolved (Thompson, Carl & Holmes ; Ruan ; Kelly ).…”
Section: Resultsmentioning
confidence: 52%
“…It has been shown that these compounds may interact to influence excitability at several levels (59,60), thus influencing excitability in both normal and dementing aging individuals. Much more work remains to be done to explain and hopefully prevent the human observational studies on increased seizure susceptibility during aging (61). The nature of seizures in the elderly might differ from those observed earlier in the life cycle.…”
Section: How Aging Influences Seizuresmentioning
confidence: 99%